Larangan’s Batik Week: An Effort to Keep and Develop Local Batik in South Larangan-Tangerang in Cooperation with Mayang Batik Community - Rukmono Budi Utomo; Faradilla Septiyani Puspita; Dita Aprilia; Yasika Egi Putri; Alya Dinda Fadhila (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
This Paper is an output of our social empowerment in South Larangan, Tangerang. This program granted by Muhammadiyah higher education through RisetMu batch V year 2022. Our issue why we did this program only caused the reason that the existence larangan’s batik has to keep and develop of its motive. We used collaborative method as our approach perspective to run this program. We develop larangan’s batik motive namely Holy Water and added some ingredients such as mathematics geometry and Crow motive. For this program run well, we are in cooperation with Mayang Batik Community which is they are community in South Larangan focused to create and making batik especially Larangan’s batik. As a result, we are success develop motive Larangan’s into 2 new motive Larangan’s batik added mathematics geometry, Kowak, and Muhammadiyah logo